Cell and Cell‐Free Mechanistic Studies on Two Gold(III) Complexes with Proven Antitumor Properties. Issue 12 (23rd January 2017) - Nardon, Chiara; Boscutti, Giulia; Gabbiani, Chiara; Massai, Lara; Pettenuzzo, Nicolò; Fassina, Ambrogio; Messori, Luigi; Fregona, Dolores
Abstract : AuL10 ([Au III Cl2 (dmdt)], dmdt = N, N ‐dimethyldithiocarbamate) andAuL12 ([Au III Br2 (esdt)], esdt = ethylsarcosine dithiocarbamate) are two extremely promising gold‐based anticancer compounds. Their mechanisms of action are still largely unknown although some specific hypotheses have been proposed. To shed light on their reactivity with probable biological targets, we report here on their interactions with serum albumin and calf‐thymus DNA, taken as model biomolecules. Quite unexpectedly, spectrophotometric investigations revealed substantially different patterns of interaction for these two gold complexes with the aforementioned biomolecules, probably arising from differences in redox chemistry. Afterwards, AuL12 was tested against A549 human non‐small‐cell lung carcinoma cells, evaluating its real‐time profile of cell‐growth inhibition by means of the xCELLigence Real‐Time Cell Analysis system. Measures of impedance by non‐invasive gold microelectrodes at the base of each well indicated that this gold complex inhibits cell proliferation after only 4 h of treatment, producing its cytotoxic effects probably at the membrane level. Abstract : Two Au–dithiocarbamato complexes are promising anticancer agents. Spectrometric studies revealed different patterns of interaction with HSA and ctDNA as model biomolecules, likely due to differences in redox chemistry. One complex was tested against A549 lung carcinoma cells using an xCELLigence Real‐Time Cell Analysis system; measures of impedance by non‐invasive Au microelectrodes showed that the complex inhibits cell proliferation after only 4 h.